Barries to Effective Listening of Company Leaders in Medan City - Emilia Ramadhani; Dewi Kurniawati; Dayana Dayana (RIRAI Publisher, 2020)
Listening is as important as speaking or giving a speech to an audience.Very few leaders realize that conversation determines the growth and productivity of the organization / company they lead. Most people also believe that they have heard effectively in a conversation, which is one of the main elements in effective communication. This type of research was quantitative descriptive analysis. This research was conducted on the core implementers (managerial and executives from various divisions) from several companies or organizations in the city of Medan, as many as one hundred (100) respondents who worked in the fields of education, health, community service, law, hospitality, and entrepreneurship. Data collection techniques were carried out in two ways, namely by using a questionnaire and google form. Google form was used only for leaders who have very limited time because of their work. Then a short interview was conducted relating to the answers given. For data analysis, quantitative descriptive analysis techniques was used using figures or pictures showing the magnitude of the numbers or frequencies of the answers provided and followed by data reduction and drawing conclusions. The results showed that almost all respondents believed that they had heard effectively. But in reality this was not the case. Most leaders experienced personal interference where they always tried to be an entertainer when listening to the other person. As listeners, their minds were always preoccupied with finding ways to make the other person feel valued, happy and approved.